?-Statistical convergence on time scales - Yilmaz, Emrah; Altin, Yavuz; Koyunbakan, Hikmet (Watam Press, 2016)
In this study, we will define ?-density of a set and ?-statistical convergence on an arbitrary time scale. Moreover, some relations about these new notions are also obtained. Copyright © 2016 Watam Press.